2007
DOI: 10.1038/sj.ejhg.5201915
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of Wolf–Hirschhorn syndrome using array CGH indicates a high prevalence of translocations

Abstract: Wolf-Hirschhorn syndrome (WHS) is caused by deletions involving chromosome region 4p16.3. The minimal diagnostic criteria include mild-to-severe mental retardation, hypotonia, growth delay and a distinctive facial appearance. Variable manifestations include feeding difficulties, seizures and major congenital anomalies. Clinical variation may be explained by variation in the size of the deletion. However, in addition to having a deletion involving 4p16.3, previous studies indicate that approximately 15% of WHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 30 publications
5
87
0
3
Order By: Relevance
“…About half of the patients with WHS have a de novo simple deletion of 4p16.3, while 40-45% of patients with WHS have an unbalanced translocation with both a deletion of 4p and a partial trisomy of a different chromosome arm [18]. South et al [19] conducted two studies, which demonstrated that the rates of unbalanced translocations involving 4p in WHS is certainly higher than reported previously and is approximately 45% [19].…”
Section: Discussionmentioning
confidence: 93%
“…About half of the patients with WHS have a de novo simple deletion of 4p16.3, while 40-45% of patients with WHS have an unbalanced translocation with both a deletion of 4p and a partial trisomy of a different chromosome arm [18]. South et al [19] conducted two studies, which demonstrated that the rates of unbalanced translocations involving 4p in WHS is certainly higher than reported previously and is approximately 45% [19].…”
Section: Discussionmentioning
confidence: 93%
“…7 Translocations between chromosomes 4 and 8 occur more frequently than expected. [7][8][9][10][11] WHS is characterized by pre-and postnatal growth delay, microcephaly, seizures, hypotonia, developmental delay, congenital anomalies and a recognizable facial appearance, which includes: hypertelorism, protruding eyes, epicanthus, arched eyebrows, prominent nasal bridge, downturned corners of the mouth, micrognathia and short philtrum, and, with increasing age, a more prominent nose. Dental anomalies, some occurring in more than half of WHS patients, have been described: delayed eruption and hypodontia, retained primary teeth, peg-shaped teeth and taurodontism.…”
Section: Wolf-hirschhorn Syndrome (Whs; Omim 194190) Is a Contiguous mentioning
confidence: 84%
“…WHS is most often caused by terminal deletions, however, interstitial deletions, unbalanced translocations and complex genomic rearrangements account for a significant proportion of cases. 2,5 The majority of 4p deletions are non-recurrent. Genotype-phenotype correlation studies have shown a relationship between deletion size and severity of clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…8,11 Beyond this region, the loss of additional critical genes appears to be responsible for variably present features, such as congenital malformations or hearing loss. 1,5,8 The identification of patients with atypical 4p deletions has provided key insight into which regions of 4p16.3 may (or may not) contribute to the pathogenesis of WHS. For example, small terminal deletions (up to 400 kb) have been inherited from phenotypically normal individuals; [12][13][14] indicating that monosomy of this region is likely benign.…”
Section: Introductionmentioning
confidence: 99%